Perspectiva neurocognitiva da ansiedade química na educação básica e superior: o que precisamos saber? - Silva, Kleyfton Soares da (2020)
The chemistry science is situated in a school position that may or may not generate anxiety. On the positive side, it can sharpen students' curiosity, whereas, on the contrary, it can be perceived as difficult to be understood, given the didactic choices made to transpose it from nature to the classroom. The aim of this paper is to understand chemical anxiety, aiming to characterize its definition, etiology, types and levels, as well as to present some examples of how to circumvent it in the classroom. It was decided to carry on a bibliographical investigation, considering that We did not find Brazilian references on this topic. Considering that the human capacity to regulate emotions, their own thoughts and behaviors, evidence shows that it is possible to lower levels of chemical anxiety through pedagogical strategies that favor the development of students' self-confidence.